Autonomous QoS Management and Policing in Unmanaged Local Area Networks - Köhnen, Christopher; Überall, Christian; Rajarajan, Muttukrishnan; Jäger, Rudolf; Rakočević, Veselin (Journal of Computer Networks and Communications, 2015)
The high increase of bandwidth-intensive applications like high definition video streaming in home and small office environments leads to QoS challenges in hybrid wired/wireless local area networks. These networks are often not QoS aware and may contain bottlenecks in their topology. In addition, they often have a hybrid nature due to the used access technology consisting of, for example, Ethernet, wireless, and PowerLAN links. In this paper, we present the research work on a novel autonomous system for hybrid QoS in local area networks, called QoSiLAN, which does not rely on network infrastructure support but on host cooperation and works independently of the access technology. We present a new QoS Signalling Protocol, policing and admission control algorithms, and a new lightweight statistical bandwidth prediction algorithm for autonomous resource management in LANs. This new QoS framework enables link based, access-medium independent bandwidth management without network support. We provide evaluation results for the novel bandwidth prediction algorithm as well as for the QoSiLAN framework and its protocol, which highlight the features, robustness, and the effectiveness of the proposed system.